NETWORK ELITE PURI AGUNG UBUD DALAM ASPEK RELIGIUS, EKONOMI, DAN POLITIK - Guna Wintara, I Gusti Ngurah; Ali Azhar, Muhammad; Jayanthi Mertha, A.A Sagung Mirah Mahaswari (Jurnal Nawala Politika; 2021: Jurnal Ilmu Politik 2021, 2020)
This research aims to determine how the elites Puri Agung Ubud network in religious, economic and political aspects. Furthermore, the research is framed using elites theory by Suzanne Keller and Barry Wellman social network theory. The research method used is descriptive qualitative method using primary data and secondary data, because it describes and describes the form of relations and the elites network of Puri Agung Ubud. The results of the research are: first, the Puri Agung Ubud elites form religious relations through their power in religion and customs, form economic relations through their power in the tourism sector, and the 2018 Pilgub formed political relationships with non-political elite. The two network of the elites are: religious network, political party network, artist network, historical network, economic network, hobby network, campus network, and social network.   Keywords :Network, Elite, Puri Agung Ubud,Religious, Economy, Political